Konsep Media Pembelajaran Matematika Berbasis Video Pada Materi Pokok Lingkaran - Diah Selviani (Universitas Dehasen Bengkulu, 2022)
Alkarim Junior High School (SMP) Bengkulu City. Research which is a qualitative descriptive type. In this study, data collection techniques were carried out by means of Observation, Interview, Questionnaire and Documentation. When teaching students, the teacher goes through three stages, namely the initial, core and closing stages. This research produces the concept of learning media, who uses learning media, stages of making learning media and internal and external factors. Video-based Mathematics learning media is applied, in the implementation of learning in the room, students are seen to be active and enthusiastic in participating in learning because the teacher uses video-based media by sending videos via Android with attractive displays and media during learning, so that learning is very interesting.